ACKR3 regulates platelet activation and ischemia-reperfusion tissue injury - Rohlfing, Anne-Katrin; Kolb, Kyra; Sigle, Manuel; Ziegler, Melanie; Bild, Alexander; Münzer, Patrick; Sudmann, Jessica; Dicenta, Valerie; Harm, Tobias; Manke, Mailin-Christin; Geue, Sascha; Kremser, Marcel; et al. (Nature Communications, 2022)
Platelet activation plays a critical role in thrombosis. Inhibition of platelet activation is a cornerstone in treatment of acute organ ischemia. Platelet ACKR3 surface expression is independently associated with all-cause mortality in CAD patients. In a novel genetic mouse strain, we show that megakaryocyte/platelet-specific deletion of ACKR3 results in enhanced platelet activation and thrombosis in vitro and in vivo. Further, we performed ischemia/reperfusion experiments (transient LAD-ligation and tMCAO) in mice to assess the impact of genetic ACKR3 deficiency in platelets on tissue injury in ischemic myocardium and brain. Loss of platelet ACKR3 enhances tissue injury in ischemic myocardium and brain and aggravates tissue inflammation. Activation of platelet-ACKR3 via specific ACKR3 agonists inhibits platelet activation and thrombus formation and attenuates tissue injury in ischemic myocardium and brain. Here we demonstrate that ACKR3 is a critical regulator of platelet activation, thrombus formation and organ injury following ischemia/reperfusion.